Comparative Assessment of Lignan, Tocopherol, Tocotrienol and Carotenoids in 40 Selected Varieties of Flaxseed (Linum usitatissimum L.) - Wu, Zhimin; Li, Yazhi; Qiu, Huajiao; Long, Songhua; Zhao, Xinlin; Wang, Yufu; Guo, Xinbo; Baitelenova, Aliya; Qiu, Caisheng (Foods, 2023)
Multiple varieties of flaxseeds have been identified in the world, yet the relationship between these varieties, their agronomic traits, and their seeds’ quality remains unclear. This study aimed to determine the level of lignan, vitamins and carotenoids in 40 selected flaxseed varieties, and the relationship between varieties, agronomic traits, and seed quality was investigated. In this study, notably, fiber flax variety No. 225 exhibited the highest lignan content among all tested seeds. Additionally, oil variety No. 167 demonstrated the highest level of α-tocotrienol (α-T3), β-tocopherol (β-T), γ-tocotrienol (γ-T3), and β-carotene (β-Car.). Conversely, intermediate flax variety No. 16 displayed the highest content of α-tocopherol (α-T), but lowest content of lutein (Lut.), zeaxanthin (Zea.), β-carotene (β-Car.), and total carotenoids (Total Car.). Furthermore, a correlation was observed between petal color with the lignan, while a strong correlation has been explored in seed yield, seed type, plant natural height, and fiber content in straw. Nevertheless, further investigation is required to elucidate the internal relationship between varieties with compositions.